PARAMETRI KOJI UTIČU NA BRZINU PLIVANJA NA DEONICI 100m KRAUL TEHNIKOM KOD STUDENATA FAKULTETA SPORTA I FIZIČKOG VASPITANJA - Goran Dimitrić; Borislav Obradović; Goran Vasić (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2010)
The aim of this study was to find what parametars affect on swimming speed on 100m crowl on students. Total of 66 students, at the age of 21 -23, participated in this research. There were 6 criterion variables from specific motoric skills as well as one predictive variable, swimming speed on 100m crowl. We have concluded that speed - endurance, swimming with legs and swimming technique significantly contribute for successful swimming on 100m crowl. These facts should use trainers to know how to improve work with students and get better swimming results on 100m crowl.